Immunological characterization of chicken tumor necrosis factor-α (TNF-α) using new sets of monoclonal antibodies specific for poultry TNF-α. (June 2022) - Lu, Mingmin; Lee, Youngsub; Li, Charles; Lillehoj, Hyun S.
Abstract: Tumor necrosis factor-α (TNF-α) is a type II transmembrane protein with either membrane-bound or soluble forms and is a prototypical member of the TNF superfamily. TNF-α is a pleiotropic cytokine associated with the regulation of systemic inflammation and host defense. Chicken TNF-α (chTNF-α) is a long-missed avian ortholog, and its immunological properties remain largely unknown compared to those of its mammalian counterparts. Here, we report the functional characterization and immunomodulatory properties of chTNF-α using a panel of newly developed anti -chTNF-α mouse monoclonal antibodies (mAbs). Using anti -chTNF-α mAbs, we determined the tissue expression of chTNF-α in lymphoid and non-lymphoid organs. A chTNF-α-specific antigen-capture sandwich ELISA was developed using compatible mAb partners by screening and validation of ten different mAbs. Employing 3G11 and 12G6 as capture and detection antibodies, respectively, the levels of native chTNF-α in the circulation of Clostridium perfringens, Eimeria, or dual C. perfringens / Eimeria -infected chickens were determined. Furthermore, intracellular expression of chTNF-α in primary immune cells or cell lines derived from chickens was validated by immunocytochemistry and flow cytometry assays using both 3G11 and 12G6 mAbs. Notably, both 3G11 and 12G6 neutralized chTNF-α-induced nitric oxide production in chicken HD11 cells in vitro . Collectively, our results enhance our understanding of the functional characteristics of chTNF-α, and these anti -chTNF-α mAbs will serve as valuable immune reagents to inform on inflammatory responses and disease pathogenesis in the fundamental and applied studies of avian species. Highlights: Tissue expression of chTNF-α in lymphoid and non-lymphoid organs was determined using anti -chTNF-α mAbs. A capture ELISA assay was developed to detect circulating chTNF-α in C. perfringens -, Eimeria -, and NE-afflicted birds. The cellular sources of chTNF-α were investigated, and intracellular chTNF-α expression was identified. Anti -chTNF-α mAbs inhibited chTNF-α-induced nitric oxide production in HD11 cells.